Free radical photopolymerization process for fiber‐reinforced polymer: Effect on the mechanical properties. (26th December 2018) - Hasiaoui, Basma; Ibrahim, Ahmad; L'Hostis, Gildas; Gautier, Karine; Allonas, Xavier; Croutxé‐Barghorn, Céline; Durand, Bernard; Laurent, Fabrice
Abstract : Glass–fiber‐reinforced polymers were manufactured either through a room temperature thermal curing or under ultraviolet (UV) light from a LED. The thermal system yields high performances when a post‐curing process at 65°C is applied. The photochemical curing leads to a composite in a faster timescale, albeit at the extent of the mechanical properties. It is found that in this case, impregnation and vacuum steps are too fast to allow a good wetting of the fibers, thereby leading to mechanical weaknesses and larger void volume. However, when applying longer vacuum and impregnation steps, the mechanical properties of the photochemically cured sample match the best thermally cured one. As a conclusion, it is shown that photochemical curing of glass–fiber‐reinforced polymer can lead to high performance composite provided that the preparation steps are well controlled.